The Determinants of Success in Black Economic Empowerment Transactions in South Africa - Hundah, Joseph (My University, 2011)
Black Economic Empowerment (BEE) has been hailed as a necessity and as absolutely critical to the country’s development but it has also been scorned upon as apartheid in reverse. The complex socio-economic issues surrounding BEE make it a very difficult topic to research. This study explores the determinants of success for BEE transactions. In-depth, semi-structured interviews were used to obtain the views of BEE participants, executives of acquired companies and BEE consultants. The main findings were that motives, the finance structure of transactions, effective leadership, the perceptions of BEE, cultural fit between partners, the operational influence of BEE participants and the structure of broad-based schemes were the main determinants of success for BEE transactions. Finally, it was also found that BEE transactions are very diverse and as such it is important to determine the circumstances of each transaction and determine which determinants are most appropriate.
MBA - WBS
Keywords: Black economic empowerment